2013
DOI: 10.1108/pr-jan-2012-0009
|View full text |Cite
|
Sign up to set email alerts
|

Age as moderator in the relationship between HR development practices and employees’ positive attitudes

Abstract: Purpose -Drawing on social exchange theory, prior research suggests that the adoption of human resources (HR) practices in the areas of training and development helps to maximize employees' positive work attitudes. However, while research has generally assumed that HR practices influence all employees in the same way, there is much evidence that employees' motives and needs change with age, suggesting that older workers may react differently to the same HR practices as compared to younger colleagues. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 70 publications
2
39
1
1
Order By: Relevance
“…Similarly, although younger employees may be lured by possibilities of promotion and the higher income associated with motivation-enhancing practices, these are less likely to appeal to older ones, either because their career perspectives are more limited (Ng & Feldman, 2013) or they give less importance to the performance feedback designed to improve their output and professional development (Findley, Giles, & Mossholder, 2000), or simply because they may have already reached the top of the ladder and have fewer financial concerns (Kanfer & Ackerman, 2004). Finally, whereas younger employees may welcome the participation-enhancing practices that allow gaining experience, developing a broad view of the organisation, and expanding their personal social network (Baron & Kreps, 1999), older ones tend to attach less value to this, given their lower expectations of advancement (Innocenti, Profili, & Sammarra, 2013;Kooij, Jansen, Dikkers, & De Lange, 2010) and their preference for dealing with colleagues they already know (Drabe et al, 2015) and value more (Fung et al, 2001).…”
Section: Workforce Ageing Hpws and Retention Ratementioning
confidence: 99%
“…Similarly, although younger employees may be lured by possibilities of promotion and the higher income associated with motivation-enhancing practices, these are less likely to appeal to older ones, either because their career perspectives are more limited (Ng & Feldman, 2013) or they give less importance to the performance feedback designed to improve their output and professional development (Findley, Giles, & Mossholder, 2000), or simply because they may have already reached the top of the ladder and have fewer financial concerns (Kanfer & Ackerman, 2004). Finally, whereas younger employees may welcome the participation-enhancing practices that allow gaining experience, developing a broad view of the organisation, and expanding their personal social network (Baron & Kreps, 1999), older ones tend to attach less value to this, given their lower expectations of advancement (Innocenti, Profili, & Sammarra, 2013;Kooij, Jansen, Dikkers, & De Lange, 2010) and their preference for dealing with colleagues they already know (Drabe et al, 2015) and value more (Fung et al, 2001).…”
Section: Workforce Ageing Hpws and Retention Ratementioning
confidence: 99%
“…On average, people generally stop being described as young at approximately 40 years of age (Abrams, Vauclair & Swift, 2011). Age represents the evolutions taking place in people's life over time, in terms of biological, psychological and social functioning (Innocenti, Profili & Sammarra, 2013). Thus, age is related with affective and normative occupational commitment because the age of an individual in terms of affective commitment is an indicator of them getting a better position in the organisation or profession and gaining tenure (Benligiray & Sonmez, 2013).…”
Section: Age As An Antecedent Of Employee Commitmentmentioning
confidence: 99%
“…Human Resource Management (HRM) can have a fundamental role in age-diversity management by creating and adapting organizational policies and practices that contribute to the alignment between workers' needs and the organization's strategy and mission (Hertel et al, 2013;Riach, 2009). In fact, previous investigation has shown that workers' age has an effect on the associations between perceived human resources (HR) practices and job attitudes and behavior (Innocenti et al, 2013;Kooij et al, 2010;Kooij et al, 2013). Researchers have been especially striving to understand how organizations can encourage older workers to stay active for longer and to postpone retirement (e.g., Armstrong-Stassen and Ursel, 2009;Bal et al, 2012;Pak et al, 2019).…”
Section: Introductionmentioning
confidence: 99%